Más allá de los modos. La experiencia de la «movilidad sostenible» en las periferias populares de Lima - Robert, Jérémy (2024)
This article discusses on the sustainability of daily mobility from the analysis of inhabitant’s practices of two popular peripheral areas of the city of Lima. It provides an analysis of experiences with the use of «sustainable» modes (walking, cycling and public transport) and «unsustainable» modes. A number of obstacles related to distance, slope or insecurity are highlighted, as well as their influence on mobility strategies and the choice of modes. The characteristics of the environment and the mobility needs in the popular peripheries do not facilitate the use of so-called «sustainable» modes, compared to «unsustainable» modes such as mototaxis, taxis or colectivos, even combis, which greatly ease the mobility of people despite constraints in terms of security and cost.